EFEKTIVITAS PERMAINAN FINGER PAINTING DAN ORIGAMI TERHADAP PERKEMBANGAN MOTORIK HALUS PADA ANAK PRA SEKOLAH DI TK NIDZAMIYAH MOJOROTO KOTA KEDIRI - Siswi Wulandari (Program Studi Kesehatan Masyarakat Universitas Sari Mutiara Indonesia, 2020)
Development (development)is the increasing ability or function of all organ systems of the body as a result of increased maturity or maturity of the function of the body's organ system. The research design used is pre-experimental research with pre-test and post-test approaches. The population studied was all children numbered 46 children with purposive sampling techniques obtained a sample of 36 respondents. The research instrument used is KPSP. The results of the study were then analyzed using Wilcoxon signed rank. The results of the analysis showed that there is an influence, while the results of the analysis of differences in the effectiveness of origami and Finger Painting on child development. It is expected that pre-school age child educators can make origami games as an effort to improve children's fine motor because it is considered more effective than finger painting.